1992
DOI: 10.1007/bf00184800
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of diarrhoea in human immunodeficiency virus-infected patients with immunoglobulins from bovine colostrum

Abstract: Diarrhoea and weight loss are found in more than 50% of patients with the acquired immunodeficiency syndrome (AIDS). In some patients the symptoms can be very severe, leading to death even in the absence of opportunistic infections. In 30% of these patients, enteric pathogens cannot be identified, and approximately only half of the identifiable aetiologic agents of diarrhoea in patients infected with the human immunodeficiency virus (HIV) were treatable with antibiotics. Immunoglobulins from bovine colostrum (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
77
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(79 citation statements)
references
References 27 publications
1
77
1
Order By: Relevance
“…First, Ig in the BSC may have facilitated a reduction in number of viable parasites. Previous studies in human cryptosporidiosis have shown efficacy of immune bovine colostrum in some studies (20) and lack of efficacy in others (21). In our study, reduced oocyst shedding in BSC-treated calves was seen, but oocysts remained in the stool at the end of the study.…”
Section: Bovine Serum Concentrate For Cryptosporidiosiscontrasting
confidence: 44%
“…First, Ig in the BSC may have facilitated a reduction in number of viable parasites. Previous studies in human cryptosporidiosis have shown efficacy of immune bovine colostrum in some studies (20) and lack of efficacy in others (21). In our study, reduced oocyst shedding in BSC-treated calves was seen, but oocysts remained in the stool at the end of the study.…”
Section: Bovine Serum Concentrate For Cryptosporidiosiscontrasting
confidence: 44%
“…Despite exhaustive attempts at chemotherapy with a wide variety of drugs, including many that are effective against related apicomplexan parasites, no efficacious treatment for cryptosporidiosis has been identified. Passive immunotherapy with hyperimmune bovine colostral immunoglobulin (HBC Ig) has, however, shown some ability to ameliorate the clinical symptoms of disease in humans (29,62,77,88,93,(108)(109)(110). HBC Ig inhibits sporozoite invasion in vitro and neutralizes sporozoite infectivity in animal models of cryptosporidiosis (5, 9, 10, 23, 69-71, 84-86, 107).…”
mentioning
confidence: 99%
“…Higher doses of a product derived from colostrum of nonimmunized cows have previously been effectively employed in AIDS patients with chronic diarrhea due to Cryptosporidia 30 or of unknown etiology. 31,32 However, the poor clinical condition of BMT recipients may reduce the possibility of exploring the benefits of dose escalation. A possible strategy for improving a future therapeutic preparation would be to increase the concentration of antibodies against crucial surface determinants on the yeast cells such as adhesion molecules and/or to deliver with excipient to increase mucosal adherence and dwelling time.…”
Section: Discussionmentioning
confidence: 99%